Discovery of Cryptophasa Lewin, 1805 (Lepidoptera: Xyloryctidae) from Indonesia with the descriptions of three new species - Sutrisno, Hari; Watung, Jackson F; Suwito, Awit (Zootaxa, 2015)
Three new species of Cryptophasa Lewin, 1805 are described from eastern Indonesia: C. watungi Sutrisno & Suwito, 2015 sp. nov., C. kwerbaensis Sutrisno & Suwito, 2015 sp. nov., and C. choliki Sutrisno & Suwito, 2015 sp. nov. Each species is described based on adult external and genital characters. The potential apomorphic character in male genitalia of Cryptophasa, the shape of the uncus, is discussed.